2022
DOI: 10.15302/j-sscae-2022.02.025
|View full text |Cite
|
Sign up to set email alerts
|

Development Practice and Breakthrough Path of China's Intelligent Manufacturing

Abstract: Intelligent manufacturing has become an unavoidable developmental trend in modern manufacturing and is the primary focus of the China Manufacturing 2025 Strategy. Moreover, it is the only method for China's manufacturing industry to go from large to strong. Investigating intelligent manufacturing breakthrough paths is critical for fostering the high-quality development of China's manufacturing industry and accelerating industrial transformation. It is also necessary to practice the "four orientations." In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
(5 reference statements)
0
0
0
Order By: Relevance
“…Long Yuntao, Huang Tingting, and others (2021) analyzed the root causes of bottlenecks that restrict the development of domestic industrial software in China and proposed that improving the innovative ecological environment (intellectual property protection, government tax exemptions) can improve the development of industrial software [32]. When Zhou Yong, Zhao Dan, et al (2022) analyzed the development of China's industrial software industry, they believed that preferential tax policies, support for software trade, and other forms could enhance the development of China's industrial software [33]. When Guo Chaoxian, Miao Yufei, and others (2022) analyzed the current competitiveness level of China's industrial software industry, they proposed ways to increase government loan support, insurance subsidy support, application reward and subsidy support, and intellectual property protection to improve industrial software industrial development [25].…”
Section: In Terms Of Environmental Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Long Yuntao, Huang Tingting, and others (2021) analyzed the root causes of bottlenecks that restrict the development of domestic industrial software in China and proposed that improving the innovative ecological environment (intellectual property protection, government tax exemptions) can improve the development of industrial software [32]. When Zhou Yong, Zhao Dan, et al (2022) analyzed the development of China's industrial software industry, they believed that preferential tax policies, support for software trade, and other forms could enhance the development of China's industrial software [33]. When Guo Chaoxian, Miao Yufei, and others (2022) analyzed the current competitiveness level of China's industrial software industry, they proposed ways to increase government loan support, insurance subsidy support, application reward and subsidy support, and intellectual property protection to improve industrial software industrial development [25].…”
Section: In Terms Of Environmental Factorsmentioning
confidence: 99%
“…The development trend of the industry in foreign and domestic representative provinces (Jiangsu and Guangdong) was analyzed, and it was pointed out that the talent structure of industrial software practitioners is a key factor affecting the development of the industrial software industry [31]. When Zhou Yong, Zhao Dan, et al (2022) analyzed the breakthrough path of industrial software development, based on the development situation of China's industrial software industry, they believed that supporting the training of industrial software talents could improve the development of China's industrial software [33]. Guo Chaoxian, Miao Yufei, and others (2022) found that the competitiveness level of China's industrial software industry needs to be improved compared with European and American countries; they believe that paying attention to the talents of industrial software companies can improve the development level of the industrial software industry [25].…”
Section: In Terms Of Human Factorsmentioning
confidence: 99%